Data-Driven Robust Feedback Control Design for Multi-Actuator Hard Disk Drives. Issue 37 (2022) - Surya Prakash, Nikhil Potu; Horowitz, Roberto
Abstract: A Data-driven feedback control framework in the frequency domain is used to design track following controllers for multi-actuator hard disk drives using the frequency response measurements of the plants. With this framework, multiple plant measurements can directly be used for the design of a common controller instead of plant models to improve robustness and avoid model mismatch. The data driven approach utilizes either the H∞ norm or the H2 norm related to the closed loop transfer functions as the control objective for a convex optimization problem along with H∞ and H2 norm constraints. The H∞ norm is used to shape the closed loop transfer functions and ensure closed loop stability. The H2 norm is used to constrain and/or minimize the variance of the relevant signals in time domain. The design methodology is demonstrated on a triple-stage hard disk drive.